Catching of mantis shrimp (Lysiosquillina maculata) by fishermen of Tanakeke Islands based on Technical Domains - Akbar, Akbar; WULANDARI, SRI (Sangia Research Media and Publishing, 2025)
Mantis shrimp (Lysiosquillina maculata Fabricus, 1793) is a type of marine crustacean that has high nutritional content, especially protein, so it is quite in demand by the international community as a consumption ingredient. Mantis shrimp is an interesting species because it has true economic and ecological value. The development of mantis shrimp fisheries in the Tanakeke Islands and Kanalo Islands can provide broad benefits, both in terms of economy and social. Ecosystem Approach to Fisheries Management is here to realize fisheries management that balances socio-economic aspects and the utilization of fish resources fairly, with knowledge, information, and uncertainty regarding biotic, abiotic components, and human interactions in aquatic ecosystems to realize integrated, comprehensive, and sustainable fisheries management. This study aims to examine the capture of mantis shrimp Based on EAFM in the Fishing Technique Domain. This study is classified as mixed methods according to the indicators set for the Fishing Technique domain, namely the frequency of violations over the past five years; Catching; area of fishing area, and duration of fishing; legal documents of the fishing fleet; and fishing vessel crew certificates. The selection of research respondents was based on purposive sampling. The condition of the mantis shrimp fishery according to the Ecosystem Approach to Fisheries Management (EAFM) approach shows an aggregate value of 290 which produces a Domain value of 93.55. This value is included in the model category with a Dark Green flag, which indicates that the implementation of EAFM is at a very good level.